RData and Rscript for the wolverine example - Milleret, Cyril; Dupont, Pierre; Bonenfant, Christophe; Brøseth, Henrik; Flagstad, Øystein; Sutherland, Chris; Bischof, Richard (Dryad Digital Repository, 2018)
WolverineData.RData is the RData file necessary to perform the analysis of the wolverine data. Script.pdf is a Rmarkdown document with the steps necessary to reproduce the analysis.